2021
DOI: 10.1101/2021.03.05.433782
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pharmacological targeting of a PWWP domain demonstrates cooperative control of NSD2 localization

Abstract: NSD2 is the primary enzyme responsible for the dimethylation of lysine 36 of histone 3 (H3K36me2), a mark associated with active gene transcription and intergenic DNA methylation. In addition to a methyltransferase domain, NSD2 harbors two PWWP and five PHD domains believed to serve as chromatin reading modules, but their exact function in the regulation of NSD2 activity remains underexplored. Here we report a first-in-class chemical probe targeting the N-terminal PWWP (PWWP1) domain of NSD2. UNC6934 binds pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 52 publications
(91 reference statements)
0
21
0
Order By: Relevance
“…Indeed, efforts have already been made to develop an inhibitor of PHIP BD2 function ( Cox et al 2016 ). Recent studies have demonstrated that targeting a single reader domain in a multivalent chromatin protein can be sufficient to disrupt normal localization ( Dilworth et al 2021 ). Thus, our characterization of the substrate specificity of each reader domain in PHIP may open up additional approaches to target its function.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, efforts have already been made to develop an inhibitor of PHIP BD2 function ( Cox et al 2016 ). Recent studies have demonstrated that targeting a single reader domain in a multivalent chromatin protein can be sufficient to disrupt normal localization ( Dilworth et al 2021 ). Thus, our characterization of the substrate specificity of each reader domain in PHIP may open up additional approaches to target its function.…”
Section: Discussionmentioning
confidence: 99%
“…Further structure-based optimization resulted in 103 (UNC6934), that showed a potent binding to PWWP1 (K D of 91 nM). 268 In order to better understand the binding mode of 103, a representation of the main interaction has been reported in Figure 29. The crystal structure of the inhibitor in complex with NSD2-PWWP1 (PDB 6XCG) shows how the cyclopropyl is inserted in a hydrophobic pocket made of Val230 and Phe266.…”
Section: Nsd1 Nsd2 Nsd3 Inhibitorsmentioning
confidence: 99%
“…Another recent study by the same group reported UNC6934 ( 34 ) as a first-in-class potent chemical probe that inhibits the interaction of NSD2-PWWP1 with the H3K36me2 nucleosome by selectively binding to the aromatic cage of the PWWP1 domain of NSD2 methyltransferase. Using the crystallographic information on NSD2 in complex with compound 32 and further molecular docking simulations, the group identified compound 33 (MRT866) containing a benzoxazinone bicyclic ring ( K d = 349 nM).…”
Section: Design and Medicinal Chemistry Of Nsd Inhibitorsmentioning
confidence: 99%
“…Using virtual screening and biophysical assays initially, they identified a chiral compound, 29, which showed selective interaction with the PWWP1 domain of NSD2 (K d = 41 μM). Based on the initial data on 29, the group designed a series of compounds using a ligand-guided scaffold hopping to find an improved active Another recent study by the same group 98 reported UNC6934 (34) as a first-in-class potent chemical probe that inhibits the interaction of NSD2-PWWP1 with the H3K36me2 nucleosome by selectively binding to the aromatic cage of the PWWP1 domain of NSD2 methyltransferase. Using the crystallographic information on NSD2 in complex with compound 32 and further molecular docking simulations, the group identified compound 33 (MRT866) containing a benzoxazinone bicyclic ring (K d = 349 nM).…”
Section: Design and Medicinal Chemistry Of Nsd Inhibitorsmentioning
confidence: 99%